Coupling Effect of Unit Cell Topology and Forming Orientation on the Ti6Al4V Porous Structures Fabricated Using Selective Laser Melting. Issue 2 (31st October 2018) - Huang, Xina; Zhang, Sheng; Hu, Quandong; Lang, Lihui; Gong, Shuili; Nielsen, Karl Brian
Abstract : Selective laser melting (SLM) opens the possibility to produce porous structures with designed mechanical characteristics. This study focuses on the coupling effect between unit cell topology (Dode and body‐centered cubic (BCC)) and forming orientation (horizontal and vertical) with regard to the actual geometric characterization and mechanical properties of SLM produced Ti6Al4V porous structures. The results show that for the mechanical response, there is a coupling effect between forming orientation and unit cell topology. This is most pronounced for the Dode topology, where the compressive and yield strength for specimens produced in vertical orientation are increased with 14.6% and 7.5% compared with those build horizontally. However, for the BCC topology, this effect cannot be seen. The fatigue properties for specimens processed vertically are better compared with those processed horizontally, especially for the BCC topology, it shows an increase of 51.6%. This study presents initial findings on how to handle the selection of unit cell topology and forming orientation for porous structures prepared using SLM, which may be beneficial for different applications. Abstract : This paper focuses on the coupling effect between unit cell topology (Dode and body‐centered cubic (BCC)) and forming orientation (horizontal and vertical) with regard to the actual geometric characterization and mechanical properties of Selective laser melting (SLM) produced Ti6Al4V porous structures.